(untitled) (Plant Tissue Culture and Biotechnology, 2008)
Aseptically, shoot bud and undifferentiated cultures of globe artichoke were successfully stored for 12 months at 5ÂºC in the dark. Under these conditions, high percentage of cultures remained viable without perceptable serious signs of senenscence. Although the rates of regrowth slightly decreased, the recovery percentages were enough to obtain high frequencies of healthy globe artichoke (= Cynara scolymus L.). The storage at cold and dark conditions was strongly effective compared with storage in the medium under osmotic stress. Also, the differentiated cultures registered a higher viability compared to undifferentiated cultures. RAPD analysis suggests that plantlets derived from the preserved cultures were identical to those derived from nonstored differentiated tissues culrtures. However, undifferentiated (callus) cultures showed relatively less genetic variation. Key words: Globe artichoke, Germplasm, In vitro preservation DOI = 10.3329/ptcb.v17i1.1115 Plant Tissue Cult. & Biotech. 17(1): 1-9, 2007 (June)